2016
DOI: 10.1103/physrevlett.116.171101
|View full text |Cite|
|
Sign up to set email alerts
|

Is the Gravitational-Wave Ringdown a Probe of the Event Horizon?

Abstract: The right bottom panel of Fig. 4 in the main text refers to the Lorentz factor E = 1.01 and not to E = 1.5 as reported in the letter. For completeness, we show here the waveforms for both E = 1.01 and E = 1.5. All our conclusions remain unchanged. Is the Gravitational-Wave Ringdown a Probe of the Event Horizon? It is commonly believed that the ringdown signal from a binary coalescence provides a conclusive proof for the formation of an event horizon after the merger. This expectation is based on the assumption… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

22
541
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 681 publications
(565 citation statements)
references
References 52 publications
22
541
1
1
Order By: Relevance
“…However, Cardoso et al [40] also realized that the later portion of the ringdown of highly compact ECOs contains a train of decaying echo pulses (note that similar observations have been made before; see for example [44][45][46]). The time delay between the echoes is related to the ECO compactness while the decay and shape of each pulse encodes the reflective properties of the ECO.…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations
“…However, Cardoso et al [40] also realized that the later portion of the ringdown of highly compact ECOs contains a train of decaying echo pulses (note that similar observations have been made before; see for example [44][45][46]). The time delay between the echoes is related to the ECO compactness while the decay and shape of each pulse encodes the reflective properties of the ECO.…”
Section: Introductionmentioning
confidence: 88%
“…In this appendix, we computeRðωÞ for a wormhole [40] describing two Schwarzschild spacetimes of mass M identified with a thin shell of exotic stress-energy at an areal radius r 0 corresponding to a tortoise coordinate location of x 0 . Note that the value ofR depends on our phase convention, and we use that of Eq.…”
Section: Appendix C: Wormhole Reflectivitymentioning
confidence: 99%
See 1 more Smart Citation
“…The cooperative efforts coming from both "classical", electromagnetic observational astrophysics and the new gravitational wave astrophysics will substantially contribute to our future picture of supermassive black holes. However, Cardoso et al (2016) point out that very compact objects with a light ring will display similar ringdown signals as black holes, implying that universal ringdown waveforms indicate the presence of light rings, rather than that of horizons. Hence, it is only that high precision measurements of the late-time ringdown signals may allow us to rule out exotic alternatives to black holes.…”
Section: (Anti)realism and Underdeterminationmentioning
confidence: 99%
“…It was reported that at a distance of about 410 Mpc in the system GW 150914 two very compact objects of about 36 M ⊙ and 29 M ⊙ merged. These objects were probably black holes; however, exotic alternatives still need to be ruled out (see sections 5 and 3.1, Cardoso et al (2016), as well as a comment in The LIGO Scientific Collaboration and The Virgo Collaboration (2016)). For most of the alternative theories, predictions for the specific shape of the ringing signal still need to be performed, although at a higher frequency, these measurements validate the method proposed to search for supermassive binary black holes and support the possibility of detection gravitational wave ringing from such systems.…”
Section: Gravitational Wave Signals From Inspiraling Objectsmentioning
confidence: 99%